2006
DOI: 10.1186/1477-7800-3-18
|View full text |Cite
|
Sign up to set email alerts
|

Good outcome after neoadjuvant chemotherapy and extended surgical resection for a large radiation-induced high-grade breast sarcoma

Abstract: This article is a case report of a high grade, radio-induced, breast malignant fibrous histiocytoma (undifferentiated high grade pleomorphic sarcoma), which developed in a 44-year old female, seven years after breast conservative surgery and radiotherapy for a T1N0M0 invasive left breast ductal carcinoma. The sarcoma presented as a fast growing tumour, 9.5 cm in the largest diameter, with skin, left breast, chest wall muscle and rib invasion.Neoadjuvant chemotherapy was performed with epirubicin and ifosfamide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
(20 reference statements)
0
8
0
1
Order By: Relevance
“…Centralization of care to specialist sarcoma reconstructive units and tissue biobanking would facilitate the development of clinical trials and studies into the cancer biology of RAAS. The roles of adjuvant chemotherapy, and hyperfractionated and accelerated radiotherapy warrant further study. Furthermore, the implementation of a national registry to identify patients with RAAS is needed, in order to establish its true incidence, investigate potential risk factors related to dose, fractionation and duration of radiotherapy regimens, and monitor the outcomes of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Centralization of care to specialist sarcoma reconstructive units and tissue biobanking would facilitate the development of clinical trials and studies into the cancer biology of RAAS. The roles of adjuvant chemotherapy, and hyperfractionated and accelerated radiotherapy warrant further study. Furthermore, the implementation of a national registry to identify patients with RAAS is needed, in order to establish its true incidence, investigate potential risk factors related to dose, fractionation and duration of radiotherapy regimens, and monitor the outcomes of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…At present, neoadjuvant therapy finds it primary use in patients with unresectable or marginally resectable disease. Quadros et al [80] reported favorable outcomes for neoadjuvant chemotherapy followed by surgery to treat RIS. However, this was the only published article identified in our systematic literature search discussing outcomes of neoadjuvant chemotherapy in RIS patients.…”
mentioning
confidence: 99%
“…Case report and literature reviewMoore et al (2008) [64] 5cCase reports (n ϭ 3) Case report and literature review Hanasono et al(2005) [65] 5cCase report (n ϭ 1) Case report and literature reviewRao et al (2003) [66] 5cCase reports (n ϭ 3) Case report and literature review Esler-Brauer et al(2007) [76] 5cCase report (n ϭ 1) Case report and literature reviewNakamura et al (2007) [77] 5cCase report (n ϭ 1) Case report and literature reviewMills et al (2002) [78] 5cCase report (n ϭ 2) Case report and literature reviewKunkel et al (2008) [57] 5cCase report (n ϭ 1) Case report and literature review Quadros et al (2006)[80] 5cCase report (n ϭ 1) Case report and literature reviewKuten et al (1985) [87] 5cCase report (n ϭ 7) Case report and literature reviewKhan et al (2009) [88] 5cCase report (n ϭ 1) Case report and literature reviewPlotti et al (2006) [91] 5cCase report (n ϭ 1) Case report and literature review Brenin et al (1998)[86] 5cCase report (n ϭ 1) Case report and literature reviewFeigenberg et al (2002) [100] 5cCase report (n ϭ 3) Case report and literature reviewSchulz et al (2000) [121] 5cCase report (n ϭ 3) Case report and literature reviewGivens et al (1999) [122] 5c Clinical review (n ϭ 85) Analysis of prognostic factors for RIS Okuno and Edmonson (1998)[113] 5c Case reports (n ϭ 2) Case report and literature reviewMano et al (2006) [102] 5cCase report (n ϭ 1) Case report and literature review Perez-Ruiz et al (2009)[134] 5cCase report (n ϭ 1) Case report and literature reviewGambini et al (2009) [116] 5c Case report (n ϭ 1) Case report and literature review De Giorgi et al(2010) …”
mentioning
confidence: 99%
“…UPS remains rare among breast sarcomas 8 18. Only a small number of case studies and single-centre retrospective studies of radiation-induced UPS are reported 13 19–31. Increase in the incidence of RIBS over the last decade is likely due to standard acceptance of breast conservation in 2002 with 20 years results from National Surgical Adjuvant Breast and Bowel Project 3233…”
Section: Discussionmentioning
confidence: 99%